Software Package for Determining the Capillary Adsorption Potential in Irrigated Lands - Danielyan, R. A. (ՀԱԱՀ հիմնադրամ)
In the current work, an analytical formula for determining the capillary adsorption potential (CAP) has been derived as a result of solving the moisture transfer equation. A universal software package program has been written in the Python language. The code enables to compute the values of CAP at any soil depth and at any time of irrigation for various soil parameters. To illustrate the code, the results of some numerical calculations are presented at the end of the work.
Keywords: Agricultural Engineering